Atrial function in heart transplant recipients operated with the bicaval technique. (2nd January 2016) - Bech-Hanssen, Odd; Pergola, Valeria; Al-Admawi, Mohammed; Fadel, Bahaa M.; Di Salvo, Giovanni
Abstract: Objectives : In heart transplantation (HTx) with the bicaval technique the whole right atrium (RA) is donor tissue while the left atrium (LA) consists of both donor and recipient tissue. The aims of the study were to describe atrial function in comparison with healthy controls and to identify determinants of dysfunction. Design : Forty-three patients and 30 controls were retrospectively included. Echocardiography was performed within 24 h of right heart catheterization (RHC) (HTx recipients). Results : The peak longitudinal atrial systolic strain (ɛ) described the atrial reservoir function. The LA and RA reservoir function were reduced versus controls (LA-ɛ 18 ± 8 versus 44 ± 10%; RA-ɛ 22 ± 10 versus 69 ± 17%, p  < 0.001). There were moderate relationships between atrial-ɛ and ventricular filling pressure ( r  = −0.64 for LA-ɛ; r  = −0.57 for RA-ɛ). In a multiple regression analysis the LA-ɛ was determined by pulmonary capillary wedge pressure (PCWP) and LA minimum volume index ( r  = −0.71) while RA-ɛ was dependent on the right ventricular ɛ ( r  = −0.77). Conclusions : Atrial reservoir function is markedly reduced in HTx recipients related to elevated PCWP and LA-enlargement in the LA and in the RA impaired longitudinal right ventricular function.